2022-RA-1505-ESGO Ovarian cancer retrospective European (O'CaRE) observational study: analysis of first-line (1L) outcomes in patients with ovarian cancer (OC) stratified by number of risk factors for progression. (20th October 2022) - Krell, Jonathan; Madhuri, Thumulurua K; Shaw, Danielle; McGrane, John; Anand, Anjana; Hartkopf, Andreas; Herrero, Ana; Yeoh, Cheng; Masvidal, Maria; Fumet, Jean-David; Rogmans, Gunther; Raspagliesi, Francesco; et al.
Abstract : Introduction/Background: The O'CaRE study assessed real-world burden of disease, treatment patterns, and outcomes in patients with OC in 5 European countries (UK, France, Germany, Spain, and Italy). The analysis presented provides real-world data on the cumulative impact of risk factors (RFs) on disease progression and survival following 1L treatment. Methodology: O'CaRE was a multicentre, noninterventional retrospective medical chart review study of patients aged ≥18 years diagnosed with epithelial ovarian, fallopian tube, or primary peritoneal cancer from 1 January 2014 to 31 December 2015. Patients were classified into moderate- or high-risk categories based on number of RFs for progression (Table). High-risk patients were further grouped by total number of RFs. Patients were followed from index date (date of diagnosis) until last activity or study end (maximum follow of 4 years). Kaplan-Meier methodology was used to estimate progression-free survival (PFS) and overall survival (OS). Results: The analysis included 412 patients: 7 (1.7%) had moderate risk of progression, whereas 405 (98%) had high risk of progression ( table 1 ). For those with high risk, 84 (20.4%), 133 (32.3%), 139 (33.7%), and 49 (11.9%) had 1, 2, 3, and 4 RFs, respectively. Median PFS was 31.3 months for patients with 0 RFs and 12.6, 7.9, 5.9, and 3.5 months for patients with 1, 2, 3, or 4 RFs, respectively. Median OS was 41.9 months for patients with 0 RFs and not reached, 25.0, 18.0, and 7.4 months for patients with 1, 2, 3, or 4 RFs, respectively. Conclusion: This real-world analysis of patients with OC from 5 European countries demonstrated that higher numbers of RFs were associated with shorter median PFS and OS. This analysis provides real-world data relating to 1L treatment outcomes for patients with OC; if validated in clinical trials, the number of RFs could be a stratification factor for future 1L OC trials.